An Atypical Presentation of Lichen Planus-Like Reaction from Pembrolizumab. (7th July 2019) - Lee, Matthew; Seetharamu, Nagashree
Abstract : Introduction . With the advent of immunotherapy, a new subtype of side effects called IRAEs or immune related adverse effects have become more common. They may present in various organ systems as colitis, pneumonitis, hypophysitis, and thyroiditis and commonly as dermatological reactions. Case . This is a case report of a lung cancer patient that was started on Pembrolizumab and developed shortly after what appeared to be clinically at first pustular psoriasis but on biopsy was confirmed to be lichen planus. She was discontinued on the Pembrolizumab and treated with both systemic and topical steroids and improved. Conclusion . This case highlights a cutaneous reaction from Pembrolizumab and the subsequent management that helped resolve her condition but also weighing the benefits against the risk of treatments and potential prognostic implications of having cutaneous side effects.